Pengaruh Pengembalian Hasil Tes Sejarah Terhadap Hasil Belajar Siswa Kelas VII SMP Negeri 6 Ambon - Gesia Mira Urlialy (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
Principal problems in this study is, Is there any effect of the return of the test results on learning outcomes of students in the subjects of history class VII SMP. 6 Ambon, in order to determine whether there is influence refund learning outcomes of students who test history returned higher than the results of the test of history that is not returned to the research conducted by the type of experimental research static using the two groups and only one of them treated experimental and one group subjected to the treatment.From the research, the result is no refund influence the test result history lesson on learning outcomes of students of class VII SMP. 6 Ambon